Cross-resistance Patterns to Acetyl-CoA Carboxylase Inhibitors Associated with Different Mutations in Japanese Foxtail (Alopecurus japonicus). Issue 4 (25th May 2017) - Chen, Guoqi; Wang, Lingyue; Xu, Hongle; Wu, Xibao; Pan, Lang; Dong, Liyao
Abstract : Japanese foxtail is a grass weed in eastern China. This weed is controlled by fenoxaprop- P -ethyl, one of the most common acetyl-CoA carboxylase (ACCase)-inhibiting herbicides. Some Japanese foxtail populations have developed resistance to fenoxaprop- P -ethyl, owing to target-site mutations (amino acid substitutions) located within the carboxyl transferase domain of ACCase. In the present study, three mutations were detected in three fenoxaprop- P -ethyl–resistant Japanese foxtail populations: Ile-1781-Leu in JCJT-2, Ile-2041-Asn in JZJR-1, and Asp-2078-Gly in JCWJ-3. Two copies of ACCase ( Acc1-1 and Acc1-2 ) were identified, but mutations were detected only in Acc1-1 . The derived cleaved amplified polymorphic sequence (dCAPS) method detected these mutations successfully in Japanese foxtail. The mutation frequencies in JCJT-2, JZJR-1, and JCWJ-3 were approximately 98%, 92%, and 87%, respectively. Different cross-resistance patterns to ACCase inhibitors were found in the three resistant populations. JCJT-2 (Ile-1781-Leu) and JZJR-1 (Ile-2041-Asn) showed cross-resistance to haloxyfop- R -methyl, clodinafop-propargyl, and pinoxaden, but were susceptible to clethodim. JCWJ-3 (Asp-2078-Gly) showed cross-resistance to all tested ACCase-inhibiting herbicides.